Congenital diseases of communication according to the DSM-V: updates child neuropsychology - Kevin Egúsquiza Vásquez (Interacciones)
In this article, updates related to communication disorders, strictly congenital character, are described, according to the latest reviews published by the American Psychiatric Association in its ﬁfth edition, which considered the main contributions of neuroscience, based on the research conducted around the theme of neurodevelopmental disorders, which during the past two decades, have attracted widespread scenario of possibilities for greater understanding of the various changes in the area of psychological development, redeﬁning and clarifying more precisely those relevant characteristics of the various related clinical conditions. Furthermore, these studies have contributed to revealing ﬁndings, both syndromic and symptomatic level, for a better understanding of these early development disorders, being highly relevant contributions in the ﬁeld of child neuropsychology, which integration of clinical and educational strategies has favored its relevant participation in treatment on these difﬁculties, thereby strengthening the exercise of differential diagnosis and rehabilitation of those procedures, which rigor is based on the controlled use of modern methods and approaches related to this discipline.